Metabolic Control of Epigenetics and Its Role in CD8+ T Cell Differentiation and Function - Yerinde, Cansu; Siegmund, Britta; Glauben, Rainer; Weidinger, Carl (Frontiers in Immunology, 2019)
Epigenetic programs that control posttranslational modifications of histone proteins and DNA itself tightly regulate transcriptional networks determining the identity and function of CD8+ T cells. Chromatin-modifying enzymes such as histone acetyltransferases and deacetylases, represent key molecular determinants of the epigenetic imprinting of CD8+ T cells. The functions of these enzymes highly depend on the availability of key products of cellular metabolism pathways such as acetyl-CoA, NAD (Nicotinamide adenine dinucleotide), SEM (S-adenosylmethionine), suggesting that there is a close crosstalk between the metabolic and the epigenetic regulation of CD8+ T cells. In this review, we will discuss the metabolic regulation of CD8+ T cell epigenetics during activation and differentiation. We will furthermore summarize how metabolic signals from the tumor microenvironment (TME) shape the epigenetic landscape of CD8+ T cells to better understand the mechanism underlying CD8+ T cell exhaustion in anti-tumor and anti-viral immunity, which might help to overcome limitations of current CD8+ T cell-based therapies.